2022
DOI: 10.3390/pathogens11101208
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Effects of Nippostrongylus brasiliensis and Its Derivatives against Atherosclerosis in ApoE-/- Mice through Anti-Inflammatory Response

Abstract: Atherosclerosis (AS) is a dominant and growing cause of death and disability worldwide that involves inflammation from its inception to the emergence of complications. Studies have demonstrated that intervention with helminth infections or derived products could modulate the host immune response and effectively prevent or mitigate the onset and progression of inflammation-related diseases. Therefore, to understand the molecular mechanisms underlying the development of atherosclerosis, we intervened in ApoE-/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(59 reference statements)
0
0
0
Order By: Relevance
“…However, the effect of AS intervention on uridine has not been reported. In ApoE −/− mouse models, two routes of administration of ES or uridine were used for anti-atherosclerosis evaluation and significant protective effects were produced by ES and uridine, which were manifested in the induction of an anti-inflammatory environment and the alleviation of AS development, which is similar to our previous study with N. brasiliensisinfected interventions [20]. No differences were observed between different routes of administration.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the effect of AS intervention on uridine has not been reported. In ApoE −/− mouse models, two routes of administration of ES or uridine were used for anti-atherosclerosis evaluation and significant protective effects were produced by ES and uridine, which were manifested in the induction of an anti-inflammatory environment and the alleviation of AS development, which is similar to our previous study with N. brasiliensisinfected interventions [20]. No differences were observed between different routes of administration.…”
Section: Discussionsupporting
confidence: 78%
“…Our previous study has also shown that N. brasiliensis -derived products can stimulate macrophages with M2 polarization in vitro [ 19 ]. Furthermore, in the AS model (ApoE −/− mouse on high-fat diet), N. brasiliensis infection or its derived products could induce an anti-inflammatory state and effectively inhibit the occurrence and development of AS, as evidenced by reduced aortic arch plaque areas and liver lipid contents, downregulated serum low-density lipoprotein (LDL), and upregulated anti-inflammatory cytokine levels (IL-10 and IL-4) manifested in serum [ 20 ]. However, interventions with direct helminth infection or its derived mixed products could have several concerns including ethical constraints, safety considerations, and not guaranteed effects.…”
Section: Introductionmentioning
confidence: 99%